A note on the modelling of MSY-related parameters when population dynamics are stochastic - Punt, Andre E. (J. Cetacean Res. Manage., 2023)
A method is outlined for calculating the values for the parameters which determine MSYR and MSYL in the types of population dynamics models on which Implementation Simulation Trials and Evaluation Trials are based in the face of environmental variability in fecundity (birth rate) and survival. The method is illustrated using a minke whale-like biology in which MSYR is defined in terms of harvesting of the mature female component of the population. Results are shown for various levels of environmental variation in survival and fecundity